From margins to mainstream: decolonizing science and promoting diversity for the future of STEM - Roksana Khalid; Isaiah J. Ting (Frontiers in Education)
Decolonizing science is essential for dismantling entrenched biases that privilege Western methodologies and marginalize valuable contributions from non-dominant regions. These historical and ongoing barriers perpetuate systemic inequalities across STEM fields, hindering diverse voices and restricting the scope of global scientific discovery. Examples within STEM illustrate the reciprocal influence of diverse cultures in shaping scientific knowledge, underscoring that progress is a collaborative, multicultural effort. Entrenched attitudes, often rooted in implicit biases, sustain the notion that scientific excellence is synonymous with famous Western names, further marginalizing diverse contributions. To foster a more inclusive and equitable scientific landscape, radical reforms in educational systems are necessary, integrating non-Western perspectives and encouraging a more comprehensive view of science. Addressing these structural barriers and shifting existing attitudes will create a global scientific community that values diverse contributions and promotes holistic, inclusive advancements in human knowledge.